2020
DOI: 10.5937/gp24-22613
|View full text |Cite
|
Sign up to set email alerts
|

What will prevail within citybreak travel, motivation or demotivation?: Case study of Novi Sad, Vojvodina, Serbia

Abstract: The aim of this paper is to develop a new perspective on urban tourist motivations and demotivation's by applying the Analytic Hierarchy Process (AHP) model in order to better understand how tourists make decisions about which destinations to visit. Authors discovered that most important factor within city break travel is internal force, followed by the external force and least important is demotivation. The paper argues that the results indicate the value of applying the AHP model to understand the role and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 112 publications
3
15
0
2
Order By: Relevance
“…The highest mean values of answers are related to the following statements: Novi Sad acts as a pleasant place to live, has a good gastronomic offer, is an attractive place for education and People are kind and hospitable (items with an average value over 4.20). This is an expected finding, considering that Novi Sad is a university city, known for its friendly population, a good gastronomic offer that was created under the influence of the multicultural environment of the city, as well as a medium-sized city pleasant for the life of citizens (Vujičić et al, 2020). Besides, current findings showing generally high mean scores (around 4) for assessment of the city as a place that isan attractive tourist destination and has an interesting architecture could be associated with previous one (Stylidis et al, 2016) that indicates residents' appreciation for the environment that is aesthetically appealing, which, as such, contributes to their better performance of daily activities.Another similarity exists with previous studies that indicated high locals' perception of the friendly environment of their residing place or country (Henkel et al, 2006).…”
Section: Resultsmentioning
confidence: 71%
“…The highest mean values of answers are related to the following statements: Novi Sad acts as a pleasant place to live, has a good gastronomic offer, is an attractive place for education and People are kind and hospitable (items with an average value over 4.20). This is an expected finding, considering that Novi Sad is a university city, known for its friendly population, a good gastronomic offer that was created under the influence of the multicultural environment of the city, as well as a medium-sized city pleasant for the life of citizens (Vujičić et al, 2020). Besides, current findings showing generally high mean scores (around 4) for assessment of the city as a place that isan attractive tourist destination and has an interesting architecture could be associated with previous one (Stylidis et al, 2016) that indicates residents' appreciation for the environment that is aesthetically appealing, which, as such, contributes to their better performance of daily activities.Another similarity exists with previous studies that indicated high locals' perception of the friendly environment of their residing place or country (Henkel et al, 2006).…”
Section: Resultsmentioning
confidence: 71%
“…Given a pairwise comparison, the AHP analysis involves three tasks: 1) developing a comparison matrix at each level of the hierarchy starting from the second level and working down, 2) computing the relative weights for each element of the hierarchy, and 3) estimating the consistency ratio (CR) to check the consistency of the judgment (Božić et al 2018;Vujičić et al 2020). If the consistency ratio (CR) is less than 0.10, the result is sufficiently accurate and there is no need for adjustments in comparison or for repeating the calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the range of different approaches that have been developed to explain tourist motivations, the push-pull theory tends to be one of the most widely referred to in the tourist motivation literature [48][49][50][51]. Although some authors have begun to reconsider the complex interactions and relationships that exist between push and pull factors [41,[52][53][54], it is generally observed that they relate to two separate tourist decisions made at two separate points in time-one focusing on whether to go or not, and the other on where to go. Therefore, push factors are perceived to be present in the decision-making process before pull factors [55], and as such they are the focus of this research.…”
Section: Tourist Motivationmentioning
confidence: 99%